Organization of oversight for integrated control of neglected tropical diseases within Ministries of Health. - Claire Standley; Matthew R Boyce; Anna Klineberg; Gabrielle Essix; Rebecca Katz (Public Library of Science (PLoS), 2018)
Background Neglected tropical diseases (NTDs) are communicable diseases that impact approximately 1 billion people, but receive relatively little research, funding, and attention. Many NTDs have similar treatments, epidemiology, and geographic distribution, and as a result, the integration of control efforts can improve accountability, efficiency, and cost-effectiveness of programs. Here, we examine the landscape of efforts towards NTD integration across countries with the highest burden of disease, and review the administrative management of integration in order to identify approaches and pathways for integration. Methodology and principal findings We utilized a standardized system to score countries for NTD endemnicity to create a list of 25 countries with the highest overall burden of NTDs. We then conducted a literature review to characterize the NTD control programs in the focus countries. Six countries were selected for key informant interviews to validate literature review results and gather additional data on opportunities and obstacles to NTD integration, from an administrative perspective. The majority of countries included in the study were located in Africa, with the remainder from Asia, North America, and South America. Multiple models and pathways were observed for the integration of NTD programs, in combination with other NTD programs, other diseases, or other health programs. Substantial heterogeneity existed with respect to the NTD control programs, and no country had integrated all of their NTD control efforts into a single program. NTDs that can be treated with preventative chemotherapy were frequently integrated into a single program. Leprosy control was also frequently integrated with those of other communicable diseases, and notably tuberculosis. Barriers to NTD integration may result from internal administrative obstacles or external obstacles. Conclusions Although many countries have begun to integrate NTD control efforts, additional work will be required to realize the full benefits of integration in most of the countries examined here. Moving forward, NTD integration efforts must ensure that administrative structures are designed to maximize the potential success of integrated programs and account for existing administrative processes.